2020
DOI: 10.3390/app10228173
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neutrophil to Lymphocyte Ratio with Patient Reported Outcomes in Knee Osteoarthritis

Abstract: Background: Determining the association of neutrophil to lymphocyte ratio (NLR) and clinical disease severity in patients with mild and advanced stage knee osteoarthritis (OA).Method: We analyzed clinical scores and routine hematology panels of 111 subjects with symptomatic knee degeneration: mild OA (66) who underwent knee arthroscopy and advanced OA (45) who had total replacement. Results: Compared to the advanced OA group, the mild OA group was younger (54/67), had fewer females (1.75/5.43), and better scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
4
1
2
Order By: Relevance
“…Shi et al reported that PLR could show in ammation in knee OA (12). In another study, no relationship was determined between NLR and symptomatic knee OA (13).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Shi et al reported that PLR could show in ammation in knee OA (12). In another study, no relationship was determined between NLR and symptomatic knee OA (13).…”
Section: Discussionmentioning
confidence: 92%
“…This is more evident in patients with erosive hand OA (8). There are few studies related to the parameters of uric acid (9, 10), neutrophil-lymphocyte ratio (NLR) and thrombocyte-lymphocyte ratio (PLR) in OA, and these studies have been conducted more on patients with knee OA (11)(12)(13).…”
Section: Resultsmentioning
confidence: 99%
“…This is more evident in patients with erosive hand OA [8]. There are few studies related to the parameters of uric acid [9,10], neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) in OA, and these studies have been conducted more on patients with knee OA [11][12][13].…”
Section: Early Onlinementioning
confidence: 99%
“…Padahal salah satu pemeran penting dalam patogenesis OA adalah inflamasi. 11 Proses inflamasi tersebut ditandai dengan adanya peningkatan sitokin inflamasi seperti TNF-α, dan IL-1β yang dapat menyebabkan terjadinya degradasi tulang rawan sendi dan penurunan sintesis Hyaluronic Acid (HA) akibat adanya peningkatan Reactive Oxygen Spesies (ROS), sehingga akan muncul gejala kaku dan nyeri pada sendi karena fungsi HA sendiri sebagai lubrikan dan salah satu faktor regenerasi tulang rawan sendi. 3,12 Selain itu, adanya mediator inflamasi juga akan meningkatkan aktivitas neutrophil yang menetap, dan secara bersamaan akan terjadi penurunan kadar limfosit.…”
unclassified
“…3,12 Selain itu, adanya mediator inflamasi juga akan meningkatkan aktivitas neutrophil yang menetap, dan secara bersamaan akan terjadi penurunan kadar limfosit. 11,13 Sehingga, ketika dilakukan pemeriksaan NLR akan didapatkan nilai yang meningkat pada keadaan inflamasi. Oleh karena itu, peneliti tertarik melakukan penelitian ini dengan tujuan untuk mengetahui hubungan antara derajat penyakit osteoartritis lutut dengan Neutrophil Lymphocyte Ratio (NLR) di RSU Al Fauzan Jakarta Periode 2019-2021.…”
unclassified